GOING BEYOND GREEN: EXPLORING CONSUMER BUYING BEHAVIOR TOWARDS GREEN PRODUCTS FOR SUSTAINABLE DEVELOPMENT IN THE 3RD DISTRICT OF ILOILO - Abang, Mary Jovelyn F.; Gabalonzo, Rowena L. (President University, 2024)
Growing public awareness of environmental issues is promoting acceptance of green consumption trends. To improve their reputation and draw in new customers, businesses are increasingly producing eco-friendly products. This, in turn, encourages consumers, who are becoming more informed about green marketing, to buy environmentally friendly products. The study aims at finding green marketing awareness and the extent of consumers' buying behavior toward green products. A purposive sampling technique identified 338 residents from four out of nine municipalities in Iloilo's third congressional district. Data was collected using a researcher-designed questionnaire, divided into two parts: the first focusing on the respondents' personal information and the second assessing their awareness of green products and buying behaviors. Data collection occurred from May 2022 to June 2023, targeting individuals who had previously purchased green products. The sample was categorized by age, gender, employment status, income, education, civil status, and product type. Quota sampling ensured equal representation from each municipality. Results indicate that consumers showed a 'High' level of awareness regarding green products, with their buying behavior reflecting a “great extent” of alignment with sustainable consumption values. The findings highlight a significant relationship between awareness levels and purchasing behaviors. Consumers demonstrate a high level of awareness regarding green products, which significantly influences their purchasing behavior. This strong correlation indicates that increased knowledge about environmental issues leads to more substantial consumer engagement in sustainable practices, highlighting the importance of ongoing education and effective marketing strategies to promote eco-friendly choices.